Ovulation Induction in Clomiphene Citrate Resistant Patient by Human Menopausal Gonadotrophin - AfraRehman ,FouziaRahim ,FarhanaAnjum (Journal of Rawalpindi Medical College, 2018)
Background :To find out ovulation rates, in Clomiphene citrate (CC) resistance anovulatory infertility, after administration of human menopausal gonadotrophin. Methods: In this cross sectional study 400 infertile patients of anovulation, bilateral patent fallopian tubes evidenced by HSG, normal husband semen analysis and resistant to Clomiphene citrate therapy and take at least three months consecutive unsuccessful treatment in dose >150 mg/day were incorporated. Patients were divided randomly via lottery technique into two groups. Group-A, included those subjects who received Clomiphene citrate (CC) daily from day 2 to 6 of menstrual cycle and Human Menopausal Gonadotrophin 75 IU begun from day 7 onward for 3 days intramuscularly. Group B comprised of those who received Human Menopausal Gonadotrophin alone 75 IU intramuscularly begun from day 2 of menstrual cycle, 5 injections were given on alternate day till 10th day of cycle. Follow up was done by ultrasound for follicle tracking and serum progesterone level on day 21 of the treatment cycle. Results: Mean age was 30.12±4.8 years and 30.27±4.48 years in both groups respectively without significant difference. Out of 400 patients, ovulation induction was observed in 386 patients of both groups. Among these 386, 15 patients got pregnant, 9(2.25%) from group A and 6(1.5%) from group B. Mild OHSS was seen in 12 (3%) and moderate OHSS was seen 4 (1%). Conclusion: Clomiphene Citrate with Human Menopausal Gonadotropins have a likely supportive consequences on ovulation rate contrasted to that of Human Menopausal Gonadotropin alone.